What works in promoting ‘What Works’? A comment on Sanders, Jones and Briggs - Raynor, Peter (Probation journal, 2022)
This short article is a comment on the recent proposal of a What Works Centre for probation ( Sanders, Jones and Briggs, 2021). Any new ‘What Works’ initiative needs to be informed by the patchy and uneven history of research on the effectiveness of probation in England and Wales. Problems have included, at various times, failure to keep up with research in other countries; over-dependency on government departments to conduct and fund research; poor planning and/or implementation of experimental projects; excessive managerialism, and failure to engage practitioners in a research culture. Unless they are avoided, these problems will hamper any new initiative.